Traditional Chinese medicine for heart failure with preserved ejection fraction: clinical evidence and potential mechanisms - Fan, Yujian; Yang, Zhihua; Wang, Lin; Liu, Yangxi; Song, Yulong; Liu, Yu; Wang, Xianliang; Zhao, Zhiqiang; Mao, Jingyuan (Frontiers in Pharmacology, 2023)
Heart failure with preserved ejection fraction(HFpEF) accounts for a large proportion of heart failure, which is closely related to a high hospitalization rate and high mortality rate of cardiovascular disease. Although the methods and means of modern medical treatment of HFpEF are becoming more and more abundant, they still can not fully meet the clinical needs of HFpEF patients. Traditional Chinese medicine(TCM) is an important complementary strategy for the treatment of diseases in modern medicine, and it has been widely used in the clinical research of HFpEF in recent years. This article reviews the current situation of HFpEF management, the evolution of guidelines, the clinical evidence, and the mechanism of TCM in the treatment of HFpEF. The purpose of this study is to explore the application of TCM for HFpEF, to further improve the clinical symptoms and prognosis of patients, and to provide a reference for the diagnosis and treatment of the disease.